Hubungan Perhatian Orang Tua dengan Hasil Belajar Siswa di Kelas VI SD Negeri 040530 Bunuraya Tahun Pelajaran 2021/2022 - Sevy Yodikia Br Perangin-angin; Karmila Br Karo (Departement of Mathematics Education, 2023)
The success or failure of an educational process is strongly influenced by the ongoing learning. The learning process is composed of a number of components or elements that are interrelated. These elements are teachers (educators), students (students), materials/materials, methods/methods, teaching curricula, learning facilities, study time, and learning facilities and the role of people. old. This research is entitled The Relationship between Parental Attention and Student Learning Outcomes in Class VI of SD Negeri 040530 Bunuraya for the 2021/2022 Academic Year. The purpose of this study was to see the relationship between parental attention and student learning outcomes. The results showed that parents' attention to class VI children at SDN 040530 Bunuraya Tigapanah District for the 2021/2022 academic year obtained an average score of 67.4. The score was in the Less category. There is a significant relationship between parental attention and student learning outcomes in class VI at SDN 040530 Bunuraya Tigapanah district for the 2021/2022 academic year. it can be concluded that tcount> from ttable (8.461 > 2.080) means, According to the table, namely the results of U t (partial) indicate that the significance value of the relationship between parental attention (X) to student learning outcomes (Y) is 0.201 > than 0.05 and t value is 8.461 > at 2.080 then HO is accepted and Ha is rejected. This means that there is a significant influence of parental attention on student learning outcomes.